2009
DOI: 10.1021/es803289w
|View full text |Cite
|
Sign up to set email alerts
|

Airborne Virus Capture and Inactivation by an Electrostatic Particle Collector

Abstract: Airborne virus capture and inactivation were studied in an electrostatic precipitator (ESP) at applied voltages from -10 to +10 kV using aerosolized bacteriophages T3 and MS2. For each charging scenario, samples were collected from the effluent air stream and assayed for viable phages using plaque assays and for nucleic acids using quantitative polymerase chain reaction (qPCR) assays. At higher applied voltages, more virus particles were captured from air with maximum log reductions of 6.8 and 6.3 for the plaq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(66 citation statements)
references
References 45 publications
5
61
0
Order By: Relevance
“…An LIV > 0 indicates that the penetration of viable particles is lower than would be expected based on a physical filtration mechanism alone, (28) consistent with an AM-FFR that inactivates airborne bioaerosols as they penetrate through it. An advantage of the LIV statistic is that it is a direct comparison of the viable and physical penetrations for a given respirator model.…”
Section: Viable Penetrationsupporting
confidence: 59%
“…An LIV > 0 indicates that the penetration of viable particles is lower than would be expected based on a physical filtration mechanism alone, (28) consistent with an AM-FFR that inactivates airborne bioaerosols as they penetrate through it. An advantage of the LIV statistic is that it is a direct comparison of the viable and physical penetrations for a given respirator model.…”
Section: Viable Penetrationsupporting
confidence: 59%
“…As a direct disinfection technology without filters, an electrostatic precipitator (ESP) at ± 6 kV was reported by Kettleson et al (2009) to exhibit 2-log IE of MS2 and at -10 kV it could reach above 6-log IE. However, using negative corona in ESP disinfection should be cautioned because of the formation of ozone.…”
Section: Comparison To Other Disinfection Technologiesmentioning
confidence: 99%
“…The corona inception voltage is less clear under conditions when the X-ray was turned on (X-ray-on condition). However, based on the magnitude of reduction in applied voltage shown in previous studies incorporating in situ soft X-ray irradiation (19,23,24), a corona inception voltage of approximately Ϫ5.25 kV would be expected in the X-ray-on condition (Fig. 1A).…”
Section: Resultsmentioning
confidence: 86%
“…Hogan et al (23) demonstrated both enhanced charging and improved collection efficiency of aerosolized bacteriophage MS2. In a follow-up study, molecular microbiological techniques were used to quantify the level of in-flight inactivation of bacteriophages T3 and MS2 passing through a soft-X-ray-enhanced ESP system (24).…”
mentioning
confidence: 99%